PENERAPAN PENDEKATAN PROJECT BASED LEARNING DALAM PERKEMBANGAN KETERAMPILAN DRIBBLING SEPAK BOLA - Nimrot Manalu; Alwi Siswandy Hasibuan; Fahrizal; Ibnu Furqan; Perdin Putra Hia (Universitas Negeri Medan, 2025)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) method in developing dribbling skills in soccer and its impact on students' tactical understanding and learning motivation. The research method used is a literature review, in which various scientific sources, such as academic journals, books, and conference proceedings from the last five years, are analyzed to identify the effectiveness of PjBL in the context of soccer learning. The findings indicate that PjBL positively influences student engagement in the learning process, enhances technical dribbling skills, and deepens tactical understanding of the game. Students who learn through this method are more active, highly motivated, and able to apply dribbling strategies in real-game situations compared to those using conventional methods, which tend to be repetitive and lack contextual relevance. However, challenges in implementing PjBL include the need for intensive guidance from teachers and a longer adaptation period for students with lower basic skills. Therefore, a flexible teaching strategy is necessary to tailor projects to students' abilities, ensuring optimal learning outcomes.